2018
DOI: 10.1155/2018/1983025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Curative Effect of Umbilical Cord Mesenchymal Stem Cell Therapy for Knee Arthritis in Dogs Using Imaging Technology

Abstract: Objective The aim of this study was to assess the efficacy of canine umbilical cord mesenchymal stem cells (UC-MSCs) on the treatment of knee osteoarthritis in dogs. Methods Eight dogs were evenly assigned to two groups. The canine model of knee osteoarthritis was established by surgical manipulation of knee articular cartilage on these eight dogs. UC-MSCs were isolated from umbilical cord Wharton's jelly by 0.1% type collagenase I and identified by immunofluorescence staining and adipogenic and osteogenic dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 51 publications
1
49
0
Order By: Relevance
“…To date, MSCs were successfully isolated from various tissues, and based on the source they have different properties, which should be considered when choosing the optimal stem cell therapy approach aiming at the tissue healing. In dogs, horses and cats, the most common companion veterinary patients, MSCs have been isolated from bone marrow (16)(17)(18)(19)(20)(21)(22)(23), adipose tissue (16, 17, 19-21, 23, 24), synovium (16), synovial fluid (17,21,25,26), synovial membrane (26), infrapatellar fat pad (16), umbilical cord (27)(28)(29), umbilical cord blood (19,30,31), Wharton's Jelly (19,31), muscle and periosteum (20,32), gingiva and periodontal ligament (33), peripheral blood (34)(35)(36)(37), endometrium (38), and placenta (31). In mice, MSCs were also isolated from the brain, spleen, liver, kidney, lung, muscle, thymus, and pancreas (39).…”
Section: Msc Sources Tissue Origin Of Mscmentioning
confidence: 99%
“…To date, MSCs were successfully isolated from various tissues, and based on the source they have different properties, which should be considered when choosing the optimal stem cell therapy approach aiming at the tissue healing. In dogs, horses and cats, the most common companion veterinary patients, MSCs have been isolated from bone marrow (16)(17)(18)(19)(20)(21)(22)(23), adipose tissue (16, 17, 19-21, 23, 24), synovium (16), synovial fluid (17,21,25,26), synovial membrane (26), infrapatellar fat pad (16), umbilical cord (27)(28)(29), umbilical cord blood (19,30,31), Wharton's Jelly (19,31), muscle and periosteum (20,32), gingiva and periodontal ligament (33), peripheral blood (34)(35)(36)(37), endometrium (38), and placenta (31). In mice, MSCs were also isolated from the brain, spleen, liver, kidney, lung, muscle, thymus, and pancreas (39).…”
Section: Msc Sources Tissue Origin Of Mscmentioning
confidence: 99%
“…As one of the most common companion animals, some breeds of canine including beagles are also experimental animals. With the improvement of living standards, diseases of aging in canine have become more common clinically, especially chronic diseases, such as osteoarthritis, hip dysplasia, diabetes, pancreatitis and tendonopathy [19,20]. Meanwhile, there are no particularly effective treatments for these diseases, which not only affect the quality of life of the affected animals, but also require the owners to invest a lot of energy, time and money.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most common companion animals, some breeds of canine including beagles are also experimental animals. With the improvement of living standards, diseases of aging in canine have become more common clinically, especially chronic diseases, such as osteoarthritis, hip dysplasia, diabetes, pancreatitis and tendonopathy [19,20].Meanwhile, there are no particularly effective treatments for these diseases, which not only affect the quality of life of the affected animals, but also require the owners to invest a lot of energy, time and money. Currently, many related reports have con rmed that AD-MSCs therapy in a variety of canine diseases in clinical trials have shown initial results [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%